TAX, ECONOMICS, AND BUSINESS - Kusuma, Celline Maya; Rizwan, Mohammed Z. (SYNTIFIC, 2023)
Background. The times are one of the things that affect the development of technology. There are a lot of articles discussing tax, economics, and business. As the times evolve, so does technology. ChatGPT started to attract public interest in 2023. Many people use this application for things in everyday life. Like making essays, making reviews, and many more. Research Purpose. To describe the article about tax, economics, and business. Research Method. The researcher used a literature review to gather information use of ChatGPT. ChatGPT is utilized to review several journals in the same field. Findings. Many journals focus on taxes in the last three years from 2020 to 2023. From this literature review found 9 articles with the topics tax, economics, and business. Conclusion. All of the authorsinthefieldofeconomicstend to conduct research with quantitative methods and conduct sample tests and process datato reach the right conclusions.